Collateral damage: Evolution with displacement of fracture distribution and secondary fault strands in fault damage zones - Savage, Heather M.; Brodsky, Emily E. (Journal of Geophysical Research, 2011)
We investigate the development of fracture distributions as a function of displacement to determine whether damage around small and large faults is governed by the same process. Based on our own field work combined with data from the literature, we find that (1) isolated single faults with small displacements have macrofracture densities that decay as r−0.8, where r is distance from the fault plane, (2) mature fault damage zones can be interpreted as a superposition of these r−0.8 decays from secondary fault strands, resulting in an apparently more gradual decay with distance, and (3) a change in apparent decay and fault zone thickness becomes evident in faults that have displaced more than ∼150 m. This last observation is consistent with a stochastic model where strand formation is related to the number of fractures within the damage zone, which in turn is a function of displacement. These three observations together suggest that the apparent break in scaling between small and large faults is due to the nucleation of secondary faults and not a change in process. Key Points Fracture density decreases sharply away from immature faults The density decay shallows as fault zones develop secondary strands Immature faults grow more per unit of displacement than mature faults